QUEER LIFE - A STUDY BASED ON THE CHARACTER ‘MALLI’ IN THE NOVEL RAM C/O ANANDI - Sreeja K S,; Jose, Jaison (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The changes in the socio-cultural sphere play a crucial role in shaping literature. sexual minority communities and their problems like marginalization, lack of acceptance, social segregation, sexual harassment and the survival, their ‘atypical’ (peculiar) sexual behaviour, all become the themes of Modern Literature. Sexual minorities such as Lesbian, Gay, Bisexual, and Transgender are collectively referred to as the LGBTQ community (or queer community). Among this group, the character Malli, a transgender individual, occupies a significant role in the novel Ram C/o Anandhi by Akhil P. Dharmajan.Malli’s internal and external conflicts regarding identity, denial of acceptance, familial and social segregation, sexual harassment and survival, all are beautifully written in this novel. The primary aim of the study is to analyze Malli’s identity conflicts and struggles for survival within the theoretical framework of queer life concepts.